CHANGES IN THE MECHANICAL COMPOSITION OF DEFINITE LIGHT-COLORED GRAY SOILS IN LAYERS - Khalikova Surayyo Narzullayevna (Web of Journals Publishing, 2025)
The article examines the mechanical composition of light gray soils prevalent in the soil cover of the GTL plant and the Shurtan gas complex in the Guzor massif of the Kashkadarya region. The study of the mechanical composition of Achimov and Achimov soils on the western and southern sides of the GTL plant showed that mainly large dust particles predominate. In particular, it was established that the A-chim horizon contains 36.81%, the Achim sublayer contains 40.37%, and the physical clay content in the Achim horizon is 26.73%, and in the Achim sublayer, which is light sandy, it is 26.12%. As a result of studying the achime and achime substrate of light gray soils distributed in the eastern and northern poles of the SHGKM, it was established that mainly coarse dust particles predominate. According to it, Achimovo soil is 38.28%, Achimovo soil is 41.39%, and physical clay is 27.03%, Achimovo soil is 28.68%, i.e., it is light sandy.
Keywords: Soil section, mechanical composition, sand, light sand, medium sand, light gray soil, physical sand, Image clay.